2011
DOI: 10.22358/jafs/66193/2011
|View full text |Cite
|
Sign up to set email alerts
|

The influence of dietary fatty acids on their metabolism in liver and subcutaneous fat in growing pigs

Abstract: The aim of the study was to determine the influence of fatty acids sources on their metabolism in the liver and subcutaneous fat. Four iso-energetic and iso-protein diets with different ratio of PUFA/SFA and C 18:2 n-6/C 18:3 n-3 obtained by changing part of the diet energy with plant oils (linseed or rapeseed), tallow or fish oil, were given to pigs from 60 to 105 kg body weight (BW). Pigs were slaughtered at 105 kg BW. The content of fatty acids in the liver and subcutaneous fat per 100 g tissue and the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
7
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
3
7
0
Order By: Relevance
“…This suggests that the composition of fatty acids may vary depending on the type of investigated tissues. Our suggestions are in agreement with the conclusions of other authors (e.g., Raes et al, 2004;Skiba et al, 2011).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…This suggests that the composition of fatty acids may vary depending on the type of investigated tissues. Our suggestions are in agreement with the conclusions of other authors (e.g., Raes et al, 2004;Skiba et al, 2011).…”
Section: Discussionsupporting
confidence: 94%
“…Pigs fed a diet with the moderate and the lowest concentrations of this group of fatty acids had worse Ʃn-6/Ʃn-3 ratio than recommended by the WHO. Moreover, we found that it is better to modify the fatty acid composition of pig tissues by using mixtures of fats than single oils (Raj et al, 2010;Skiba et al, 2011). Similar results have been found by other authors (e.g., Nguyen et al, 2003;Więcek et al, 2010).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations